Green synthesis of silver nanoparticles mediated Diospyros kaki L. (Persimmon): determination of chemical composition and evaluation of their antimicrobials and anticancer activities - Keskin, Cumali; Ölçekçi, Ali; Baran, Ayşe; Baran, Mehmet Fırat; Eftekhari, Aziz; Omarova, Sabina; Khalilov, Rovshan; Aliyev, Elvin; Sufianov, Albert; Beilerli, Aferin; Gareev, Ilgiz (Frontiers in Chemistry, 2023)
The eco-friendly synthesis of metallic nanoparticles (MNPs) using biological materials is an encouraging and innovativeness approach in nanotechnology. Among other synthesizing methods, biological methods are chosen because of their high efficiency and purity in many aspects. In this work, using the aqueous extract obtained from the green leaves of the Diospyros kaki L. (DK); silver nanoparticles were synthesized in a short time and simply with an eco-friendly approach. The properties of the synthesized silver nanoparticles (AgNPs) were characterized using various techniques and measurements. In the characterization data of AgNPs, Maximum absorbance at 453.34 nm wavelengths, the average size distribution of 27.12 nm, the surface charge of -22.4 mV, and spherical appearance were observed. It was determined that 0.03-0.050 µg/ml concentrations ranges of DK-AgNPs were growth suppressive concentrations on pathogen microorganisms. The MTT technique was used to study the cytotoxic effects of produced AgNPs on cancer cell lines (Glioblastoma (U118), Human Colorectal Adenocarcinoma (Caco-2), Human Ovarian Sarcoma (Skov-3) cancer cell lines, and Human Dermal Fibroblast (HDF) healthy cell line). It has been observed that they have a suppressive effect on the proliferation of cancerous cell lines. Because of the high concentration of bioactive chemicals in D. kaki, it may be employed as a biological resource in medicinal applications. DK-AgNPs were shown to be an effective antibacterial agent as well as a prospective anticancer agent. The results provide a potential approach for the biogenic production of DK-AgNPs utilizing D. kaki aqueous leaf extract.